PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP PENERAPAN GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN RETAIL (STUDI KASUS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015) - Yolanda Dian Tjandra; Ni Wayan Suryathi (Jurnal Ilmiah Akuntansi & Bisnis, 2017)
ABSTRACT There are 5 aims of this study, the first one is to find out the effect of profitability on the application of good corporate governance on retail companies. The second one is to find out the influence of the companies’ sizes on the application of good corporate governance on retail companies. The third one is to find out the effect of ownership structure of the company on the application of good corporate governance on retail companies. The forth one is to find out the effect of companies’ leverage on the application of good corporate governance on retail companies. And the last one, is to find out the influences of companies’ internal and external factors on the application of good corporate governance on retail companies. The increasing number of companies going public, will lead to tighter competition among open companies. Every company need to do a good management to win the competition. Based on the study results, it can be concluded that profitability has positive and significant impacts on the application of good corporate governance (GCG) on retail companies in BEI in the period of 2013-2015, the sizes of the company have positive and significant impacts on the application of GCG on retail companies in BEI in the period of 2013-2015, the ownership structure of the company has negative and significant impacts on the application of GCG on retail companies in BEI in the period of 2013-2015, the companies’ leverage has positive and significant impacts on the application of GCG in BEI in the period of 2013-2015. Profitability, the sizes, the ownership structure, and the leverage of the companies simultaneously have significant impacts on the application of GCG on retail companies in the period of 2013-2015. Seeing GCG as one of the factors that helps improving the companies’ performances, then it is important to apply GCG to increase public trust.Keywords: Internal Factors, External Factors, Good Corporate Governance